Spiritualitas Dalam Pendidikan Islam - Amrullah, Amrullah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This article aims to further describe how Islamic educational institutions are able to develop good spiritual values, so that graduates of Islamic educational institutions have not only intellectual intelligence but also balanced spiritual intelligence. This paper uses the liberary research method by browsing various authoritative books and journals. The results showed that spirituality in Islamic education is very important because the highest goal of Islamic education is how to produce human beings who have moral perfection (kamil people). Strengthening the spirituality of Islamic education can be done by equating perceptions of the objectives of Islamic education that lead to spirituality. Likewise, on the aspect of educators and learners also have a character of spirituality that is consistently displayed in everyday life.